The Philosophy Book - Edited by Landau, Cecile; Szudek, Andrew and Sarah Tomley (London Dorling Kindersley, 2011)
A guide to more than 2,000 years of thought. It covers the topics ranging from moral ethics to philosophies of religion.
Include Color Illustrations and Index
Keywords: Philosophy